2020
DOI: 10.14715/cmb/2020.66.4.30
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the anticancer potential of plant-food bioactives: A key focus to prostate cancer

Abstract: Prostate cancer is an international health problem and represents one of the most encountered malignancies among men. In this complex and heterogeneous disease, androgens and their receptors play a crucial role in both progression and development. Although the search for its effective treatment is still ongoing, among other priorities it requires developing better anticancer agents with greater efficacy and fewer side effects. In this regard, herbal medicines, which have been used in cancer treatment, represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…Meanwhile, some treatments for liver cancer, such as chemotherapy, have been proven to have serious side effects [10,11]. Thus, there is great interest in finding effective and safe anticancer substances from natural products, especially nutraceuticals and functional foods [12].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, some treatments for liver cancer, such as chemotherapy, have been proven to have serious side effects [10,11]. Thus, there is great interest in finding effective and safe anticancer substances from natural products, especially nutraceuticals and functional foods [12].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have consistently shown that increased dietary intake of fruits and vegetables is strongly associated with a reduced risk of developing chronic diseases such as cardiovascular disease, diabetes and cancer (3,4). Long-term intake treatment with anti-cancer plant foods is effective in reducing the patient's illness and recurrence rate of cancer compared to traditional methods of cancer treatment (5,6). Cauliflower, also known as broccoli, brassica, and tender stem cauliflower, contains high levels of sulforaphane (SFN) (7).…”
Section: Introductionmentioning
confidence: 99%